Hepatitis B vaccination in a hyper-endemic tribal community from India: assessment after three years - Murhekar, M.V.; Murhekar, K.M.; Sehgal, S.C. (Vaccine, 2004)
Hepatitis B infection is highly endemic among the primitive tribes of Andaman and Nicobar Islands, India and it is necessary to initiate hepatitis B vaccination for control of this infection. A pilot project of mass hepatitis B vaccination using indigenously developed vaccine was initiated among Nicobarese tribe of Car Nicobar Island. Sero-protection rates after second and third year were 89% and 85.5%, respectively. The rate of chronic infection in the vaccinated population after three years was 1.86% compared to the pre-vaccination rate of 20.7%. Considering high sero-protection rates and low cost, the indigenous vaccine could be used for vaccination programme in this tribal community.